Perancangan User Experience Aplikasi Pembelajaran Digital Marketing Youtube untuk UMKM menggunakan Metode Human-Centered Design - Rizky Adytia Ivan Rahman; Ratih Kartika Dewi; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Exactly on the 17th of November, 2019, a new virus was just revealed in China and then spread to the whole world. Our government imposed a large-scale social restrictions (PSBB) to reduce the spread of the virus. This pandemic is detrimental to all sectors, including MSMEs. According to a Bank Indonesia (BI) survey released in March 2021, around 87.5 percent of MSMEs in Indonesia were affected by the COVID-19 pandemic. However, BI noted that there were 12.5% ​​who were not affected by the COVID-19 pandemic because the MSMEs were transforming with digitalization. Digitization can be started using digital marketing, but there are still many MSMEs who have not done digital marketing because of the lack of knowledge about doing digital marketing using social media, for example, YouTube. This research focuses on designing the user experience (UX) of the YouTube digital marketing learning application so that the system is made according to user needs. The method used is Human-Centered Design (HCD), which is a method of solving problems by involving a human perspective. This research will produce a high-fidelity prototype which will be tested using the heuristic evaluation method. There are 3 evaluators who are experts to conduct the test which resulted in 24 usability problem findings. The usability problem is categorized based on the severity rating and then corrected the problem.